Traços de tradução em artigos de anestesiologia: uma comparação entre os resultados de um corpus paralelo e de um corpus comparável - Pinto, Paula Tavares [UNESP] (My University, 2011)
The research on “features of translation” has been favored by the observation of electronic corpora with the aid of computational tools. Since most studies about the features of translation have been based on literary texts, this article aims at discussing the presence/absence of “simplification” and “explicitation” in scientific papers. In order to do so, we will present a brief theoretical review on the universals of translation and on corpus-based translation studies. Then we will present the data gathered from a parallel and from a comparable corpus, consisting, respectively, of articles translated to English and articles originally written in English. The results have shown that the discussion on the presence/absence of translation features could, or should, also be guided by the comparison between different genres such as the literary and the academic ones.

As pesquisas sobre os “traços de tradução” têm sido favorecidas pela observação de corpora eletrônicos por meio de ferramentas computacionais. Como a maioria dos relatos sobre os traços de tradução tem sido feita com base em textos literários, o presente artigo visa a discutir a presença/ausência dos traços de simplificação e de explicitação em artigos científicos. Para tanto, será apresentada, inicialmente, uma breve revisão teórica sobre os universais da tradução e sobre os estudos da tradução baseados em corpus. Em seguida, serão apresentados os dados levantados a partir de um corpus paralelo e de um corpus comparável, compostos por artigos traduzidos e originalmente escritos em inglês. Os resultados mostram que a discussão sobre os traços de tradução poderia, ou deveria, ser pautada também pela comparação dos diferentes gêneros textuais, como o literário e o acadêmico.
Features of translation on papers of anesthesiology: a comparison between the results of a parallel and a comparable corpus
Keywords: estudos da tradução baseados em corpus; traços de tradução; tradução técnico-científica; corpus-based translation studies; features of translation; technical and scientific translation